Tele-emergency behavioural health in rural and underserved areas. (September 2021) - Weigel, Paula; Bhagianadh, Divya; Merchant, Kimberly AS; Wittrock, Amy; Rahmouni, Hicham; Bell, Amanda; Laws, Stephanie; Ward, Marcia M
Introduction: Challenges accessing behavioural health services in rural and underserved areas are compounded by severe shortages of behavioural health specialists, and difficulties placing patients. Tele-emergency (tele-ED) behavioural health is a promising solution for enhancing access to specialists and assisting in patient placement. This paper describes two tele-ED behavioural health models in the Midwest delivering mental- and substance use disorder services to rural and underserved adult populations. Methods: We performed an in-depth examination of two tele-ED behavioural health programmes and their consultation processes. We provide a retrospective case-control analysis of patient characteristics, patient diagnoses, and disposition status for each model. Data were collected from 19 spoke hospitals across the two programmes between November 2015 and December 2017. Results: Tele-ED was activated in 15% of the Avera Health sample and 58% of the Union Hospital sample. This is primarily a reflection of the sample selection process in each model and how each programme is operationalised. Suicide and/or poisoning by drugs were the most frequent diagnoses followed by mood disorders. Rate of transfer to another inpatient facility was much higher for tele-ED cases than controls in both models. Discussion: This paper describes how two distinct tele-ED behavioural health models operating in unique contexts address challenges in access and placement for patients in rural and underserved areas presenting to EDs with behavioural health conditions. The notable difference in disposition rates between cases and controls is indicative of the impact each model is having on care practices and processes.